Standardization of hydroponics fodder production technology - Sruthi Liz Thomas (Department of Agronomy,College of Agriculture, 2019)
The study entitled “Standardization of hydroponics fodder production technology” was undertaken during 2017-2019, at College of Agriculture, Vellayani, Thiruvananthapuram, Kerala, with the objectives to identify suitable fodder crops for hydroponics system and to standardize nutrient solution, seed rate and period for harvest. Research work comprised three experiments which was carried out in a low cost hydroponics fodder production system at the Integrated Farming System Research Station, Karamana, Thiruvananthapuram. The crops were grown in a hydroponics machine made of PVC pipes with 2m x 1.3m x 1.8m length, breadth and height with four shelves and automatic sprinkler irrigation system. The first experiment was aimed to evaluate the suitability of fodder crops for hydroponics. The experiment was laid out in completely randomised design and the crops included in the trial were rice (c1), barley (c2), maize (c3), wheat (c4), sorghum (c5), bajra (c6), ragi (c7), cowpea (c8), horse gram (c9) and greengram (c10). The seeds were soaked in 0.1 per cent sodium hypochlorite solution for 12 hours, tied in gunny bag and kept for germination for 24 hours. The seeds were then transferred to trays following a seed rate of 200 g ft-2 (0.22 g cm-2). Among the crops, maize recorded the highest net income and B:C ratio. Considering yield and quality, greengram recorded significantly superior GFY (10.17 kg kg-1seed), protein content (20.97 %), the lowest values for fibre and ash, and a B:C ratio more than one. In sorghum and pearl millet, seed to green fodder yield multiplication was very poor (<3 kg). Finger millet had undesirable characters for hydroponics green fodder like lower values for shoot length, shoot weight, protein content, EE and higher values for fibre and ash. Hence, maize and greengram were identified and selected for the next experiment. The second experiment was done to standardize seed rate and period of harvest of the selected crops. Three different seed rates viz, s1 : 150 g ft-2 (1.61 kg m-2), s2: 175 gft-2 (1.88 kg m-2), s3 : 200 g ft-2 (2.15 kg cm-2) and four different period for harvest viz, t1 : 7 days, t2 : 9 days, t3 : 11 days and t4 : 13 days were adopted. But, in the case of green gram, it was observed that the crop did not survive beyond nine days in hydroponic fodder production system and hence only two periods of harvest viz, t1 and t2 were taken for green gram. Both crops were separately analysed in completely randomised design with two factors. It was observed that maize sown at 200 g ft-2 (s3) and harvested on 11th day (t3) recorded significantly higher values for GFY (6.03 kg kg-1seed) and B:C ratio. While, greengram sown at 200 g ft-2 (s3) and harvested on 7th day (t1) recorded significantly higher values for GFY (10.18 kg kg-1seed) and B:C ratio. Hence, these best combinations of seed rate and period of harvest for both the crops were selected for the next experiment. The third experiment was done to standardize nutrient solution for hydroponics fodder production. The nutrient solutions tested were n1: hoagland solution (0.25%), n2: hoagland solution (0.5%), n3: 19:19:19 (0.5%), n4 : DAP (0.5%) + KCl (0.5%), n5 : starter solution (1:2:1), n6 : vermiwash (10 times dilution), n7 : groundnut cake (supernatant solution) and n8 : water (control), which was sprayed on alternate days from 3rd day. Both crops were separately analysed in completely randomised design. In green gram, spray of hoagland solution (0.25%) (n1) resulted in higher shoot weight, root weight, root length, shoot length and GFY, but the B:C ratio was less than one. Spray of 19:19:19 (0.5%) (n3) recorded on par values with hoagland solution (0.25%) (n1) for shoot weight, root weight, root length, shoot length, GFY and a significantly higher B:C ratio. In maize, spray of hoagland solution (0.25%) (n1) resulted in higher shoot weight, root weight, root length, shoot length and GFY, but a B:C ratio of less than one. The highest B:C ratio was recorded in treatment n8 i.e, water (control). From the results, it can be concluded that both maize and greengram are suited for hydroponics fodder production. Maize grown at a seed rate of 200 g ft-2 with water and harvested on 11th day, and greengram at a seed rate of 200 g ft-2, sprayed with 19:19:19 (0.5%) and harvested on 7th day were found to give the best results considering growth parameters, yield attributes, quality and economics.